Design and Implementation of Quality Information Management System for Modular Construction Factory - Shin, Jiwong; Choi, Byungjoo (Buildings, 2022)
Modular construction has been gaining increasing attention from industry and academia as a solution to the limitations of the traditional on-site orient production systems in the construction industry. Various attempts have been made to improve modular construction performance. However, while previous studies have attempted to enhance the productivity of modular construction, attempts to improve the efficiency of quality management in modular construction have been limited. Moreover, the quality management practices in a modular factory still rely on document-oriented quality information management, which is inefficient. Therefore, this study aims to develop a quality information management system to improve quality information management during module manufacturing. Accordingly, quality information during module manufacturing has been standardized using integration definition for process modeling, and system functions are defined using standardized quality information. The developed modular factory quality information management system includes module information and production-type management, material management, and module production management. The practicability and validity of the developed system were examined by accredited tests and certification laboratory and modular construction experts. The developed system is expected to contribute to improving the existing inefficient quality management process of module manufacturers by providing an integrated and systematic method to manage quality information generated during manufacturing.
Keywords: modular construction factory; off-site construction; quality information management system; quality management